Abdominal aortic aneurysm: Treatment options, image visualizations and follow-up procedures - Sun, Zhonghua (Chinese P L A General Hospital * Institute of Geriatric Cardiology, 2012)
Abdominal aortic aneurysm is a common vascular disease that affects elderly population. Open surgical repair is regarded as the gold standard technique for treatment of abdominal aortic aneurysm, however, endovascular aneurysm repair has rapidly expanded since its first introduction in 1990s. As a less invasive technique, endovascular aneurysm repair has been confirmed to be an effective alternative to open surgical repair, especially in patients with co-morbid conditions. Computed tomography (CT) angiography is currently the preferred imaging modality for both preoperative planning and post-operative follow-up. 2D CT images are complemented by a number of 3D reconstructions which enhance the diagnostic applications of CT angiography in both planning and follow-up of endovascular repair. CT has the disadvantage of high cummulative radiation dose, of particular concern in younger patients, since patients require regular imaging follow-ups after endovascular repair, thus, exposing patients to repeated radiation exposure for life. There is a trend to change from CT to ultrasound surveillance of endovascular aneurysm repair. Medical image visualizations demonstrate excellent morphological assessment of aneurysm and stent-grafts, but fail to provide hemodynamic changes caused by the complex stent-graft device that is implanted into the aorta. This article reviews the treatment options of abdominal aortic aneurysm, various image visualization tools, and follow-up procedures with use of different modalities including both imaging and computational fluid dynamics methods. Future directions to improve treatment outcomes in the follow-up of endovascular aneurysm repair are outlined.